Conquistas da fé na gentilidade brasílica : a catequese jesuítica na aldeia do Geru (1683-1758) - Santos, Ane Luise Silva Mecenas (2011)
At the turn of the 17th century the action of Jesuits towards the ―sertão‖ of the Portuguese colony in the New World intensified. The Indian villages were turned into a battlefield where local culture and knowledge shared space with the European Christian tradition. The conversion process was based on conquest for souls, land and power. The Jesuitic catechetical action on the north of the captaincy of Bahia resulted in the production of texts about the language and customs of people, who lived along the banks of the River Real. Thus, the Catechism and Grammar in the Kiriri language were written by Luiz Mamiani. These writings are important to understand the historical culture of Jesuits in the colonial period, and their contribution to the constitution of a new Christendom. Based on the relevance of such records, this work aims to point out some signs of catechesis and the method used by Mamiani. For that, this paper discusses the knowledge involved in the construction of Jesuitic historical culture in the ―sertão‖ of the captaincy of Sergipe Del Rey. Moreover, Mamiani s writings also reflect the influence of baroque rhetoric with disguised images, which showed life between two distinct worlds. In the writings of Jesuits of Geru village in Sergipe, the Christian Europe comes across the Indian Portuguese America. Two apparently distant worlds intersected in the Jesuit sermons. It is possible to see that for the conquest of the Portuguese America, they used not only firearms but also words.